PENGARUH FASILITAS DROP BOX, E-SPT DAN E-FILING DALAM PENYAMPAIAN SURAT PEMBERITAHUAN (SPT) TERHADAP KEPUASAN WAJIB PAJAK - Fitri Damayanti; Achmad Fauzi (Akuntabilitas, 2015)
This research aims to analyze and get empirical evidence about the the influenceof facilities drop box, e-SPT and e-filing submission of a letter innotice (SPT) to satisfaction oftaxpayer. Respondents in this study are taxpayers in KPP Pratama Central Jakarta Regional.The number of taxpayer that were visited in this study were 75 taxpayers from 3 KPP PratamaThe method of determining the sample is by using convenience sampling method, while thedata processing methods used by researcher is the multiple regression analysis. The resultshows the facilities drop box, e-SPT and e-filing submission of a letter innotice (SPT) partiallyinfluence to satisfaction of taxpayer.Then, facilities drop box, e-SPT and e-filing submission ofa letter innotice (SPT) simultaneously and significantly influence to satisfaction of taxpayerDOI: 10.15408/akt.v8i3.2774